Factors associated with adherence to antihypertensive agents in the older adult. - Silva Fhon, Jack Roberto; Gómez-Luján, María del Pilar; Maiara Caetano, Gideany; Sara Cáceda-Ñazco, Giovanna; Pereira dos Santos-Neto, Alexandre; Esperanza Leitón-Espinoza, Zoila (Revista Cuidarte)
Introduction: With aging, there is an increased risk of suffering from different chronic diseases, including high blood pressure. Hypertension management must be carried out by health professionals, whether or not treatment involves medication. By controlling drug treatment, especially adherence, serious health problems for older people can be avoided. Objective: To determine the factors associated with adherence to arterial hypertension treatment in older adults who live at home. Materials and Methods: A quantitative and cross-sectional study was conducted in La Libertad Region, Peru, with 342 older adults living at home. For data collection, a sociodemographic profile form, anthropometric measurements, blood pressure measurements, the Mini-mental State Examination (MMSE) test, the Geriatric Depression Scale (GDS), and the Morisky Green Levine (MGL) adherence scale were used. In addition, descriptive and analytical statistics were used. Result: 57.60% of the participants did not adhere to the pharmacological treatment, and, in most of the sociodemographic variables examined, they did not adhere to pharmacological treatment in most cases. Likewise, a relationship between retirement in older adults and the MGL adherence scale score was identified. The study showed evidence linking treatment adherence and age (p=0.01), retirement status (p=0.05), and history of stroke (p=0.004). Discussion: Treatment adherence depends on sociodemographic and health factors for disease control and a healthy lifestyle. Conclusion: Older adults and their caregivers need guidance and education to improve adherence to pharmacological treatments.